Determination of Harmful Elements in Flotation Products of a Gold Mine by ICP-MS with the Matrix-Matching Method - Qirong LIU; Bu CHU; Shuhang CHEN; Xiaoxu JIA; Zhihang ZHANG; Weining XIE; Shuai WANG; Peizhong FENG (Yankuang ceshi)
For the quantification analysis of harmful elements (such as Ni, Cu, Cd and Pb), which may have the same grade or high content as gold, the complex matrix of gold ore can produce inhibitory effects, weaken the ionization rate and signal response, and show a negative effect on measurement results. In the work described here, inductively coupled plasma-mass spectrometry (ICP-MS) with matrix-matching was applied. Compared with the standard solution of harmful elements with pure reagent, a standard solution of harmful elements in a complex matrix reduced the difference in the matrix when the solution of the sample was dissolved. The accurate determination of harmful elements was achieved with the calibration of non mass spectrometry interference by the internal standard solution and matrix-matching. Main matrix elements of each flotation product of gold ore were determined by the mineralogical analysis, and sample dissolution was conducted by the microwave digestion with HCl-HNO3-HF. Recovery rate of 10μg/L harmful element were 90%−110% in 500μg/mL and 1000μg/mL matrix solution of single and multiple types of matrix elements. Quantitative deviation of harmful elements in flotation samples of various matrix types was less than 20%, which was measured by harmful elements standard solution with single and two types of matrix elements of 1000μg/mL. Hence, the harmful element standard solution with the Fe-S matrix was applied for the determination of harmful elements in flotation products of gold ore. For the spiked recovery experiment of representative samples measured by the standard solution, the elemental spiked recovery rate ranged from 92.08% to 106.65%. Six parallel tests were conducted on representative samples, and the relative standard deviation (RSD) of each element was 1.21%−4.69%. ICP-MS with matrix matching method is suitable for quantification determination of harmful elements in flotation samples of gold ore.